Nestin mediates hedgehog pathway tumorigenesis - Li, Peng; Pfister, Stefan (Cancer research, 2016)
The intermediate filament protein Nestin serves as a biomarker for stem cells and has been used to identify subsets of cancer stem-like cells. However, the mechanistic contributions of Nestin to cancer pathogenesis are not understood. Here, we report that Nestin binds the hedgehog pathway transcription factor Gli3 to mediate the development of medulloblastomas of the hedgehog subtype. In a mouse model system, Nestin levels increased progressively during medulloblastoma formation, resulting in enhanced tumor growth. Conversely, loss of Nestin dramatically inhibited proliferation and promoted differentiation. Mechanistic investigations revealed that the tumor-promoting effects of Nestin were mediated by binding to Gli3, a zinc finger transcription factor that negatively regulates hedgehog signaling. Nestin binding to Gli3 blocked Gli3 phosphorylation and its subsequent proteolytic processing, thereby abrogating its ability to negatively regulate the hedgehog pathway. Our findings show how Nestin drives hedgehog pathway-driven cancers and uncover in Gli3 a therapeutic target to treat these malignancies. Cancer Res; 76(18); 5573-83. ©2016 AACR.